Literature Study Of Chamomile ( Matricaria Chamomilla ) For Generalized Anxiety Disordered - Fadila Anisa Perwito; Suhendriyo, Suhendriyo; Susilo Yulianto (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
Chamomile ( Matricaria chamomilla ) is one of the most widely used herbal medicines worldwide. Scientific evidence is needed to increase the use of chamomile in treating generalized anxiety disorder . This study aims to find out information from various scientific publications regarding the benefits of chamomile ( Matricaria chamomilla ) for generalized anxiety disorder . The sources of this study were obtained by collecting data from research results of journals indexed in Google Scholar, Science Direct and PubMed with publication years 2016-2021. Based on the search results, 341 journals with relevant titles were found in the Google Scholar database , 17 journals were found in Science Direct , and 5 journals were found in Pubmed . After being adjusted to the inclusion and exclusion criteria, 5 journals were selected for review. This study uses a literature study method. Based on the results of the literature that has been obtained, chamomile can be useful for reducing symptoms of generalized anxiety disorder with moderate to severe sufferers. The flavonoid content in chamomile has an anxiolytic effect that can reduce the regulation of the hypothalamic pituitary adrenal (HPA) axis. Apigenin, which is a flavonoid, specifically binds to the gamma-aminobutyric acid (GABA) receptor. The dosage forms used are chamomile extract capsules and chamomile hydroalcoholic extract .